Wireless Sensor Network in the Photovoltaic Power Generation Monitoring System - Wang Huan; Xu Xiaoli (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
The sensor layer in the monitoring and control system of Solar PV Power Generation collects PV array state information. The amount of solar PV array is so large and the distribution of solar PV array is so wide that cable connection isn’t suitable. The wireless communication technology ZigBee is a data communication network protocol based on the underlying short-range data 802.15.4, which can conveniently collect surrounding environment information and status data of photovoltaic power. DOI: http://dx.doi.org/10.11591/telkomnika.v11i8.3139